Dual-height Distribution of Ozone and Nitrogen Oxides during Summer in Urban Tianjin: An Observational Study - Tiantian Zhang; Weili Lin; Liang Ran; Zhiqiang Ma; Qing Yao; Jingle Liu; Jing Ming (Aerosol and Air Quality Research)
Abstract Measurements of gaseous pollutants, including ozone (O3) and nitrogen oxides (NOx), were simultaneously conducted at 220 m (via the installation of an air flow drainage system on a 255-m meteorological tower) and 3 m above the ground in urban Tianjin during summer 2018. The observed O3 concentrations at the two altitudes exhibited similar diurnal variations but distinctly different values, with higher levels near the surface during the day and the opposite trend at night. Generally higher concentrations of NO and NO2 were found at 3 m than 220 m, and the difference in concentration between the two altitudes for the latter pollutant was smaller during daytime and highest at night. Ox (O3 + NO2) concentration near the surface during the day, but the difference was negligible at night. Based on the higher NOx level at 3 m, the photochemical production of O3 (Ox) at low altitudes intensified during the day, suggesting that the O3 surface concentration was mainly influenced by local photochemical production. Additionally, by measuring the reactive nitrogen (NOy) near the surface and calculating NOz (NOy – NOx), the ozone production efficiency (OPE; Ox/NOz) in urban Tianjin was assessed for the first time and determined to be 6.0 ± 0.4. Compared to the values measured during summer 2010, lower levels of NOx but significantly higher ones for O3 were observed during the same season in 2018.